A aplicabilidade do método Infomapping no departamento de assuntos acadêmicos do Instituto Federal de Sergipe - Silva, Gildevana Ferreira da (2019)
This paper had a proposal to elaborate an electronic information manual for the Department of Academic Affairs of the Federal Institute of Sergipe using the Infomapping method. In order to promote the improvement of information and the process of access and retrieval of information, its application, the establishment of status indicators and the information resources developed and extinguished by the department of its main activity, the selective process of student admission. The identification of all informational resources in the sector made it possible to make process fragility more visible, as well as requiring more resource resources. The methodology used was the elaboration of a knowledge base through the process of creating a technological support tool, as well as the elaboration and use of support information for the managerial project in the sector activities area.